Muscle mitochondrial function and biogenesis with aging - Hepple, Russell (Henry Stewart Talks, 2007)
Role of mitochondria in muscle performance, Changes in skeletal muscle contractile function with aging, Effect of aging on mitochondrial oxidative capacity and its consequences, Mitochondrial dysfunction in aged muscle, Mechanisms contributing to mitochondrial dysfunction in aged muscles
Archived at 2018/10/28